2018
DOI: 10.1096/fj.201800079r
|View full text |Cite
|
Sign up to set email alerts
|

Maternal protein restriction induces gastrointestinal dysfunction and enteric nervous system remodeling in rat offspring

Abstract: Early-life adversity is a major risk factor for the development of diseases later in life. Maternal protein restriction (MPR) is associated with morbidities in offspring affecting multiple organs, but its impact on the gastrointestinal (GI) tract remains poorly studied. Using a rat model, we examined the consequences of MPR on GI function and on the enteric nervous system (ENS) in the offspring at postnatal d 35 under basal state and following a water avoidance stress (WAS). Compared with control rats, MPR rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…For instance, in female offspring from undernourished pregnant rats (8% protein diet), colonic tight junction Zonula Occludens 1 mRNA expression was decreased, without impacting on permeability to lipopolysaccharides (LPS), in comparison to offspring of pregnant rats receiving the standard 20% diet [18]. Another study with the same level of maternal protein restriction reported an increased ex vivo colonic hyperpermeability to small molecules in 35 days aged offspring [19]. In offspring from undernourished pregnant rats (receiving a 6% protein diet), the disaccharidase activity (lactase and sucrase) was increased in different segments of the intestine [41].…”
Section: Undernutrition Modelsmentioning
confidence: 99%
“…For instance, in female offspring from undernourished pregnant rats (8% protein diet), colonic tight junction Zonula Occludens 1 mRNA expression was decreased, without impacting on permeability to lipopolysaccharides (LPS), in comparison to offspring of pregnant rats receiving the standard 20% diet [18]. Another study with the same level of maternal protein restriction reported an increased ex vivo colonic hyperpermeability to small molecules in 35 days aged offspring [19]. In offspring from undernourished pregnant rats (receiving a 6% protein diet), the disaccharidase activity (lactase and sucrase) was increased in different segments of the intestine [41].…”
Section: Undernutrition Modelsmentioning
confidence: 99%
“…Low-protein diets fed during pregnancy have been shown to reduce offspring birth weight in several species [ 13 , 14 , 36 ]. Results from the current study show that exposure to a low-protein diet in utero significantly reduced the average birth weight of all live born, female and male piglets by 15%, compared to AP offspring.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains controversial whether these models adequately reflect the transgenerational effects of diet. Additionally, exposure has been conducted during both gestation and lactation [ 13 , 14 , 15 , 16 ], complicating analysis of how in utero exposure is linked to the onset of metabolic diseases later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Stress has been shown to be associated with both the onset and maintenance of GI symptoms. Furthermore, patients with GI dysfunctions have been found to be more likely to develop psychiatric disorders before the onset of GI symptoms (Mayer et al, 2001;Donald et al, 2017;Aubert et al, 2018). However, the mechanisms underlying stress-gut dysfunctions have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%